2020
DOI: 10.7554/elife.58544
|View full text |Cite
|
Sign up to set email alerts
|

Striatal direct and indirect pathway neurons differentially control the encoding and updating of goal-directed learning

Abstract: The posterior dorsomedial striatum (pDMS) is necessary for goal-directed action; however, the role of the direct (dSPN) and indirect (iSPN) spiny projection neurons in the pDMS in such actions remains unclear. In this series of experiments, we examined the role of pDMS SPNs in goal-directed action in rats and found that whereas dSPNs were critical for goal-directed learning and for energizing the learned response, iSPNs were involved in updating that learning to support response flexibility. Instrumental train… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 48 publications
4
27
0
Order By: Relevance
“…These authors hypothesized that this signal reflects a general eligibility trace. The current results extend this claim by directly linking bilateral release to the modulation of action-outcome learning, resulting, over the course of training, in the development of a lateralized signal capable of directly modulating striatal output for goal-directed performance (Peak et al, 2020).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…These authors hypothesized that this signal reflects a general eligibility trace. The current results extend this claim by directly linking bilateral release to the modulation of action-outcome learning, resulting, over the course of training, in the development of a lateralized signal capable of directly modulating striatal output for goal-directed performance (Peak et al, 2020).…”
Section: Discussionsupporting
confidence: 70%
“…The capacity for goal-directed action is a core function that allows animals to encode the consequences or outcome of their actions and so make flexible choices to maintain adaptive behavior in a changing environment (Dickinson & Balleine, 1994;Dolan & Dayan, 2013). Recent evidence suggests that action-outcome encoding depends on a prefronto-striatal circuit focused on the posterior dorsomedial striatum (pDMS) (Balleine, 2019;Balleine & O'Doherty, 2010;Hart, Bradfield, Fok, et al, 2018) with initial learning and the subsequent updating of these associations involving changes in plasticity at two types of principal neuron (Balleine et al, 2021): the striato-nigral direct spiny projection neurons (dSPNs), which express dopamine D1 receptors, and striato-pallidal indirect SPNs (iSPNs) expressing the D2 receptor (Gerfen & Surmeier, 2011) (Matamales et al, 2020;Peak et al, 2020). Importantly, this plasticity appears to reflect the integration of glutamatergic inputs from cortical, thalamic and limbic regions with the input from midbrain dopaminergic neurons (Bradfield et al, 2013;Fisher et al, 2020;Holly et al, 2019;J.…”
mentioning
confidence: 99%
“…The direct and indirect pathway SPNs encoded reward and no-reward outcomes, respectively [36]. The direct and D2/indirect SPNs were shown to be essential for initial learning of instrumental contingency and flexible update of behavior after contingency change, respectively [37, 38].…”
Section: Discussionmentioning
confidence: 99%
“…The previously discussed reduction in striatal D2 receptors fostered by restricted feeding in mice of this inbred strain is limited to the left hemisphere, and a blockade of D2 receptors in the left dorsolateral striatum is sufficient to reproduce the effects of restricted feeding on stress coping in FF mice of this inbred strain [ 42 ]. Finally, a recent study reported that optogenetic inhibition of striatal output neurons of the indirect pathway fosters perseveration in a reversal learning paradigm [ 85 ], suggesting a causal relationship between the neural and behavioral phenotypes fostered by restricted feeding in mice of the D2 strain.…”
Section: Discussionmentioning
confidence: 99%